2006
DOI: 10.1177/155005940603700306
|View full text |Cite
|
Sign up to set email alerts
|

Benign Childhood Epilepsy with Centra-Temporal Spikes: Quantitative EEG and the Wechsler Intelligence Scale for Children (WISC-III)

Abstract: Benign childhood epilepsy with centro-temporal spikes (BECTS) is a form of focal idiopathic epilepsy, with seizure remission by the age of 18. Recent studies have suggested that some children with BECTS can suffer from deficits of memory, attention and learning ability and in auditory-verbal and performance sub-tests. On the other hand, alterations in the baseline brain electrical activity determined by using the quantitative electroencephalogram (qEEG) have been described. The objective of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…The time for the first seizure was a factor in the neuropsychological results, as also with the parents scholastic level. On the other hand, factors connected to the epileptic nature of BECTS, such as the number of seizures, time since the last seizure and the CTS number and lateralization, showed no correlation with the results in the neuropsychological tests, suggesting the existence of other factors to be better investigated, such as an eventual immaturity or brain dysfunction 14 , which could be expressed in basal brain electrical activity elements 18 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The time for the first seizure was a factor in the neuropsychological results, as also with the parents scholastic level. On the other hand, factors connected to the epileptic nature of BECTS, such as the number of seizures, time since the last seizure and the CTS number and lateralization, showed no correlation with the results in the neuropsychological tests, suggesting the existence of other factors to be better investigated, such as an eventual immaturity or brain dysfunction 14 , which could be expressed in basal brain electrical activity elements 18 .…”
Section: Discussionmentioning
confidence: 93%
“…It has been discussed in the literature whether the cognitive deficit occurs due to the location of the EA in the centro-temporal region, side of the CTS, the number of CTS or even to a deficit in brain maturity, which interferes with the functional organization of the developing brain, or if it is due to activity of the focus 3,4,6,8,[14][15][16][17] . A previous study showed a relationship between immaturity in the development of brain electrical activity in children with BECTS 18 , represented by findings in the quantitative EEG, and inferior cognitive performance in the WISC-III. However, few studies have widely investigated the relation between clinical aspects of this epileptic syndrome, such as the age when the seizures started, the total number and type of seizure and the duration of the epilepsy phase, and the observed cognitive deficits.…”
mentioning
confidence: 94%
“…In children with epilepsy associated with centrotemporal spikes, higher absolute delta power correlated negatively with performance IQ at the central, temporal, parietal and occipital channels bilaterally, and higher absolute theta correlated negatively with performance IQ in all channels except right central (Tedrus et al, 2006). No correlation was found between EEG band power and verbal or full scale IQ's.…”
Section: Discussionmentioning
confidence: 96%
“…No correlation was found between EEG band power and verbal or full scale IQ's. The authors argued that their results pointed to a maturational disturbance in children with epilepsy with centrotemporal spikes that affect performance IQ but not verbal IQ (Tedrus et al, 2006). No correlation with alpha power was found, in contradistinction to findings from multiple other groups who studied only subjects without epilepsy (Gasser et al, 1983; Marosi et al, 1999; Schmid et al, 2002; Polunina and Davydov, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation